A new species of the Cyrtodactylus irregularis complex (Squamata: Gekkonidae) from Gia Lai Province, Central Highlands of Vietnam - Luu, Vinh Quang; Dung, Tran Van; Nguyen, Truong Quang; Le, Minh Duc; Ziegler, Thomas (Zootaxa, 2017)
We describe a new species of the genus Cyrtodactylus from Gia Lai Province, Central Highlands of Vietnam based on morphological and molecular differences. Cyrtodactylus gialaiensis sp. nov. is differentiated from other congeners by a unique combination of the following characters: Size small, maximum known SVL reaching 62.8 mm; dorsal pattern consisting of six or seven dark transverse bands between limb insertions; intersupranasals two or three; dorsal tubercles at midbody in 16–21 irregular rows, strongly developed on flanks; lateral folds poorly defined with interspersed tubercles; ventral scales between ventrolateral folds 38–45; precloacal pores nine or 10 in males, eight pitted scales in the adult female, in a continuous row; femoral pores absent; enlarged femoral scales present; postcloacal tubercles two or three; dorsal tubercles present to half of tail; subcaudal scales not enlarged. In molecular analyses, the new species is weakly supported as a member of the Cyrtodactylus irregularis species group with a minimum pairwise genetic distance of 13.7% from others within the group.